2007
DOI: 10.1038/sj.npp.1301385
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Improves Cognitive Deficits of Dopamine Transporter Knockout Mice without Long-Term Tolerance

Abstract: Various studies suggest a dysfunction of nicotinic neurotransmission in schizophrenia and establish that patients suffering from schizophrenia and attention deficit hyperactivity disorder (ADHD) have a high tobacco consumption, potentially for the purpose of selfmedication. Owing to its neuroprotective and procognitive effects, transdermal nicotine was proposed to be an effective treatment of some neurodegenerative and psychiatric diseases. Mice deficient in the dopamine transporter (DAT KO) exhibit a phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 82 publications
(108 reference statements)
4
29
0
1
Order By: Relevance
“…However, in humans, it has been suggested that neuropsychiatric deficits, but not normal cognitive functioning, could be improved by nicotinic treatment (Newhouse et al 2004a, b). Moreover, similarly to our results, chronic nicotine treatment was shown to affect motor functions in wild-type mice but not in mice knockout for the dopamine transporter (DAT) gene that exhibit ADHD and schizophrenia-like phenotypes, whereas such a treatment had pro-cognitive effects in DAT mutant but not in wild-type mice (Weiss et al 2007). Very interestingly, the pro-cognitive effects of chronic nicotine in both b2-/-and DAT mutant mice have been suggested to rely on a7-subunit-containing nAChRs (Besson et al 2007;Weiss et al 2007).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, in humans, it has been suggested that neuropsychiatric deficits, but not normal cognitive functioning, could be improved by nicotinic treatment (Newhouse et al 2004a, b). Moreover, similarly to our results, chronic nicotine treatment was shown to affect motor functions in wild-type mice but not in mice knockout for the dopamine transporter (DAT) gene that exhibit ADHD and schizophrenia-like phenotypes, whereas such a treatment had pro-cognitive effects in DAT mutant but not in wild-type mice (Weiss et al 2007). Very interestingly, the pro-cognitive effects of chronic nicotine in both b2-/-and DAT mutant mice have been suggested to rely on a7-subunit-containing nAChRs (Besson et al 2007;Weiss et al 2007).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, similarly to our results, chronic nicotine treatment was shown to affect motor functions in wild-type mice but not in mice knockout for the dopamine transporter (DAT) gene that exhibit ADHD and schizophrenia-like phenotypes, whereas such a treatment had pro-cognitive effects in DAT mutant but not in wild-type mice (Weiss et al 2007). Very interestingly, the pro-cognitive effects of chronic nicotine in both b2-/-and DAT mutant mice have been suggested to rely on a7-subunit-containing nAChRs (Besson et al 2007;Weiss et al 2007). A great variability in nicotine-elicited effects on behaviour is recognized and has been reported to result from the activation by nicotine of different nAChRs and neuronal pathways (Stolerman 1991;Auta et al 2000;Picciotto 2003).…”
Section: Discussionsupporting
confidence: 72%
“…For example, nicotine administration has been shown to improve attention and working memory deWcits in adults diagnosed with ADHD (Levin 2002) and nicotine agonists have been shown to reduce ADHD symptom severity (Wilens et al 2006). In addition, nicotine administration has been shown to signiWcantly alter dopamine activity and produce increased locomotor activity in genetically intact mice (Fung and Lau 1988;Grady et al 1992) and DAT1 knockout-mice (Weiss et al 2007a;Weiss et al 2007b). Given such evidence, researchers have begun to examine diVerent aspects of the nicotinergic system and nicotine receptors speciWcally, with the nicotinic acetylcholine receptor 4 subunit gene (CHRNA4) receiving the most attention thus far.…”
Section: Nicotinic Acetylcholine Receptor 4 (Chrna4)mentioning
confidence: 98%
“…These mice exhibit behaviors such as perseverative locomotor activity, stereotypy, and cognitive and behavioral inflexibility. DAT knockout mice were shown to have deficits in cognitive tasks (the cued and spatial versions of the Morris water maze) and administration of nicotine improved performance such that latencies, distance travelled, and successful trials needed to reach the platform approached levels seen in the wild type (Weiss et al 2007). …”
Section: The Dopamine Transporter Knockout Mousementioning
confidence: 96%